THEATRE ACTORS PROFESSIONAL TRAINING IN UKRAINE AND EUROPE: TERMINOLOGY ANALISYS - Mankovska, Olena (Studies in Comparative Education, 2020)
The article is dedicated to the analysis of the "professional training of future actors" concept, its components and characteristics. The author made an analytical review of scientific works of domestic researchers on the problem of professional training in general and professional training of future actors in particular. The author determined that the professional education of theatrical artists as well as general professional education includes stages of pre-professional training (acquisition of primary professional skills), primary professional training (professional education), retraining (professional training) and advanced training. The analysis of definitions of "professional training" and approaches to understanding the essence of the phenomenon in the Ukrainian and foreign scientific dimension allowed the author to establish the presence of such key components in its structure as: professional qualities, professional abilities, readiness, skill, competence and more. Defining the features of the definition of "vocational training" in the domestic and European educational dimensions, the author singled out two approaches: differential and synonymous. The author determined that in the study devoted to the professional training of theatrical art specialists it is expedient to adhere to the synonymous interpretation of the concepts "professional" and "vocational". According to the results of theoretical research, the author states that for both domestic and foreign science vocational training is a complex multifunctional process that involves the acquisition of future specialists knowledge, skills and abilities in a particular field of human activity, involves the formation of professional orientation, competence, socially significant and professionally important qualities and their integration in the process of professional activity, readiness for professional activity and professional growth, search for optimal methods of quality and creative performance of professional activity in accordance with individual psychological characteristics of the individual.